Use of a Panfungal PCR Assay for Detection of Fungal Pathogens in a Commercial Blood Culture System - Iwen, Peter C. (American Society for Microbiology, 2004)
A panfungal PCR assay was used to evaluate the ability of the ESP blood culture system to detect fungemia. The results showed that the ESP system is reliable for the detection of fungi and showed the applicability of using a molecular-based assay as a potential rapid and reliable method for the identification of fungi.